Removing cosmic-ray hits from multiorbit HST Wide Field Camera images - Windhorst, Rogier A.; Franklin, Barbara E.; Neuschaefer, Lyman W. (Publications of the Astronomical Society of the Pacific, 1994)
We present an optimized algorithm that removes cosmic rays ('CRs') from multiorbit Hubble Space Telescope (HST) Wide Field/Planetary Camera ('WF/PC') images. It computes the image noise in every iteration from the WF/PC CCD equation. This includes all known sources of random and systematic calibration errors. We test this algorithm on WF/PC stacks of 2-12 orbits as a function of the number of available orbits and the formal Poissonian sigma-clipping level. We find that the algorithm needs greater than or equal 4 WF/PC exposures to locate the minimal sky signal (which is noticeably affected by CRs), with an optimal clipping level at 2-2.5 x sigma(sub Poisson). We analyze the CR flux detected on multiorbit 'CR stacks,' which are constructed by subtracting the best CR filtered images from the unfiltered 8-12 orbit average. We use an automated object finder to determine the surface density of CRS as a function of the apparent magnitude (or ADU flux) they would have generated in the images had they not been removed. The power law slope of the CR 'counts' (gamma approximately = 0.6 for N(m) m(exp gamma)) is steeper than that of the faint galaxy counts down to V approximately = 28 mag. The CR counts show a drop off between 28 less than or approximately V less than or approximately 30 mag (the latter is our formal 2 sigma point source sensitivity without spherical aberration). This prevents the CR sky integral from diverging, and is likely due to a real cutoff in the CR energy distribution below approximately 11 ADU per orbit. The integral CR surface density is less than or approximately 10(exp 8)/sq. deg, and their sky signal is V approximately = 25.5-27.0 mag/sq. arcsec, or 3%-13% of our NEP sky background (V = 23.3 mag/sq. arcsec), and well above the EBL integral of the deepest galaxy counts (B(sub J) approximately = 28.0 mag/sq. arcsec). We conclude that faint CRs will always contribute to the sky signal in the deepest WF/PC images. Since WFPC2 has approximately 2.7x lower read noise and a thicker CCD, this will result in more CR detections than in WF/PC, potentially affecting approximately 10%-20% of the pixels in multiorbit WFPC2 data cubes.